PHARMACOGNOSTICAL INVESTIGATION ON WHEAT GRASS. - KUMAR SHANKUL; SATISH V; RAVI CHANDRA V D; RAHUL S; KAMBHOJA S; ASHUTOSH M (International Journal of Pharma and Bio Sciences, 2010)
Shoot of Triticum aestivum Linn. is also called as wheat grass, belonging to family: Gramineae. Triticum is a genus of annual and biennial grasses, yielding various types of wheat, native to southwest Asia and the Mediterranean region. T. aestivum Linn, common or Bread wheat, is widely cultivated almost all over the world. Generally, 15-20 species are recognized, of which about 8 have been reported to occur in India.It contains Polysaccharides-Glucans, Fatty oil (2%), Phospholipids (1%), Glycolipids (0.5%): particularly acyldigalactosyl glycerols, Steroids (0.3%): sterol esters, Proteins (20%), Lignin, Alkyl resorcinols (0.1 – 0.2%). The principal carotenoid pigment of wheat flour is α- dihydroxycarotene. Small quantities of flavonoids are also present in wheat germ. Two derivative of apigenin, designated flavonoid A and flavonoid B have been identified. Pharmacologically wheat is used in the treatment of cancer and in acute diarrhoea. It is also used as antifungal and antioxidant. In the present studies Pharmacognostical investigation were done on basis of transverse section, Powder analysis, and physicochemical parameter.